Antimicrobial impacts of selected Lamiaceae plants on bacteria isolated from vegetables and their application in edible films. (February 2023) - György, Éva; Laslo, Éva; Salamon, Bernadette
Abstract: Fresh vegetables can be contaminated with spoilage and food-borne pathogenic bacteria during cultivation, harvesting, transport and further processing. The essential oils seem a promising solution for preserving vegetables incorporated in edible films. During the study it was determined the prevalence of allochthonous bacteria on some fresh vegetables with classical cultivation and molecular biology techniques. The evaluation of the antibacterial effect of Thymus vulgaris, Origanum vulgare, Mentha piperita and Melissa officinalis essential oils against identified bacteria from vegetables and on some standard foodborne pathogenic bacteria was realized with agar diffusion method. The prevalence of allochthonous bacteria in the examined vegetables was diverse. In some cases, high contamination level could be detected reaching the level of 10 4 colony forming units/g. The identified bacteria belong to different genera like Bacillus, Enterobacter, Pseudomonas etc. Of the tested plant essential oils, the most pronounced antibacterial effect was detected in the case of thyme and oregano, with over 30 mm inhibition zone. The isolated bacteria from vegetables showed higher resistance to the used essential oils. The results suggest that edible films containing thyme and oregano essential oils possess efficient antibacterial effect against mesophilic aerobic bacteria and Staphylococcus aureus . These findings seem a promising solution for preserving vegetables with natural antimicrobial containing edible films.